Europe Needs a New Vision for a Natura 2020 Network. Issue 6 (25th January 2013) - Hochkirch, Axel; Schmitt, Thomas; Beninde, Joscha; Hiery, Marietta; Kinitz, Tim; Kirschey, Jenny; Matenaar, Daniela; Rohde, Katja; Stoefen, Aleke; Wagner, Norman; Zink, Andreas; Lötters, Stefan; et al.
Abstract Twenty years after the world's nations agreed upon the Convention on Biodiversity, there is still a global decline in biodiversity. At present it seems unlikely that the Aichi Targets of halting biodiversity loss by 2020 will be met. Although the European Union is often seen as a pioneer in this regard, as its "Habitats Directive" represents one of the strongest legal tools in nature conservation, biodiversity continues to decline even in Europe. We outline four major problems in the current implementation of the directive. First, prioritization needs to be based upon comprehensive scientific knowledge. This requires a maximized number of red list assessments of European species and a regular adaptation of the annexes in order to focus on those sites with the highest conservation value. Second, strategic conservation plans need to be compiled for highly threatened species and adaptive management plans need to be implemented in each reserve. Third, an improved "on‐ground" monitoring system is necessary, focusing on population trends of priority species and feeding back to management plans and red list assessments. Fourth, substantial financial resources have to be invested in the implementation as well as education in order to reach a societal consensus on the necessity for conservation.